(untitled) - Kahn, Mirim B. (Chicago, 2004)
Preventing common causes of loss -- Planning for the worst : loss of computer operations -- Basic considerations in disaster response planning -- Disaster response planning -- Disaster response : when everything goes wrong -- Disaster response planning for hardware and physical storage media -- Protecting data for long-term retention -- Decision-making for today and tomorrow -- The future : organizations involved with the study of the preservation of electronic records -- Checklists.
Keywords: Libraries,Archives,Library information networks,Electronic records,Emergency management,Computer security,Data protection,Electronic data processing; Safety measures,Safety measures,Security measures,Conservation and restoration,Planning,Backup processing alternatives